Comparative Effects of iPad and Music Glove Technologies on Learning Outcomes and Usability in Elementary Music Education - Danso, Andrew; Ansani, Alessandro; Bamford, Joshua S.; Lucendo-Noriega, Alicia; Luck, Geoff; Rousi, Rebekah; Thompson, Marc C. (Music Academy Studio Musica, 2024)
This study uses a mixed-methods approach to investigate the learning outcomes, student experiences, and concentration-related behaviour patterns of two classes of elementary school music students (N = 42). It compares the academic performance of students using an established music technology, the iPad, with those using an experimental technology, a wearable Music Glove. The results show significant improvements in musical knowledge scores for both the iPad (W = 1, p < .001) and Music Glove (W = 28.5, p = .043) groups, with the iPad group demonstrating greater improvement (d = 1.83 vs d = .48). A MannWhitney U test confirmed a significant difference in score improvements between the two groups (p < .01). Based on these findings, we propose the Technology Engagement and Adoption for Concentration and Habituation (TEACH) model, an enhancement of the original Technology Acceptance Model (TAM). The TEACH model incorporates additional constructs such as the adaptation curve, engagement, immersion, and prior experience, providing a more comprehensive framework for understanding the relationship between perceived ease of use, actual use, and learning outcomes in technology-enhanced music education. Full details of this study are available in the primary author's doctoral dissertation.
Keywords: Music education technology; Learning outcomes; Usability; Student concentration; fi=Viestintätieteet|en=Communication Studies|